The Apostle Paul and the Christian life : ethical and missional implications of the new perspective - McKnight, Scot; Modica, Joseph B. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2016)
The "new perspective" on Paul, an approach that seeks to reinterpret the apostle Paul and his letters against the backdrop of first-century Judaism, has been criticized by some as not having value for ordinary Christians living ordinary lives. In this volume, world-renowned scholars explore the implications of the new perspective on Paul for the Christian life and church. James D. G. Dunn, N. T. Wright, Bruce Longenecker, Scot McKnight, and other leading New Testament scholars offer a response to this question: How does the apostle Paul understand the Christian life? The book makes a fresh contribution to the new perspective on Paul conversation and offers important new insights into the orientation of the Christian life.
The Christian life from the perspective of Paul's Letter to the Galatians / James D.G. Dunn -- The new perspective and the Christian life in Paul's Letter to the Ephesians / Lynn H. Cohick -- Faith, works, and worship: Torah observance in Paul's theological perspective / Bruce W. Longenecker -- The new perspective and the Christian life: Solus Spiritus / Patrick Mitchel -- Participation in the new-creation people of God in Christ by the Spirit / Timothy G. Gombis -- The new perspective and the Christian life: the ecclesial life / Scot McKnight -- A symphonic melody: Wesleyan-holiness theology meets new-perspective Paul / Tara Beth Leach -- Paul and missional hermeneutics / N.T. Wright.
Includes bibliographical references and indexes.
Keywords: Christian life -- Biblical teaching; Bible. -- Criticism, interpretation, etc